Burocratização e institucionalização das organizações de movimentos sociais: o caso da organização de prostitutas Davida - Andreia Skackauskas Vaz de Mello (2007)
The discussion about the non-governamental organizations (NGO) has been developed more in the political-ideological field than in the academical-sociological one. Many have been the theories and ideological or doctrinarian formulations that try to interpret how NGO should develop in the world today and what should be their role in this contemporaneous context. Under the organization sociology light, the present study, on the contrary, tried to identify the organizational and social dimensions that affect their lives independently of the idealized visions of their leaders or intellectual mentors about their development. In order to do that, the dissertation has been restrained to the study of the Davida NGO case, a prostitutes organization in Brazil. The analysis comprehended the operational and managing structures of the organization, as well as the evaluation of its relation to other actors of the external environment; in order, this way, to analyze this NGO institutionalization. A descriptive-qualitative research was carried out, analyzing documents and conducting half-structuralized interviews. The data point out that, although it has been institutionalized, Davida has not become a big highly bureaucratized and hierarchic organizational structure; inverting Webers inevitable bureaucratization logic or the Michels Oligarchy iron law, considered by social movement theorists as factors capable of weakening the reivindicatory potential and the autonomous and informal character peculiar to the organizations that make part of a collective action. The emphasis in the burocracy and in the rationality as institutionalism dimensions permitted a simultaneous analysis of macro and micro sociologic precepts, that directed the conclusion of this work as being the institutional leadership of Davida NGO one of the principal explanatory factors for the institutionalization of this organization. Moreover, this leadership work summarizes the narrow limit between Davida NGO and the prostitutes movement, for having transformed this NGO in the strategic focus of the movement identity articulation.